Pengaruh Globalisasi Terhadap Pertumbuhan Ekonomi Di Negara Berkembang: Analisis Dampak Investasi Asing Langsung (FDI), Ekspor, dan Perdagangan Bebas Terhadap Pertumbuhan Ekonomi di Negara-Negara Berkembang - Ismail , Fadhil Fadhluraman Putra; Panjaitan , Rayner A; Marpaung, , Vriyan Holten; Kenjiroh M , Benny; Siswajanthy, S.H., M.H, Farahdinny (Sharia Journal and Education Center Publishing, 2025)
This study analyzes the impact of globalization on economic growth in developing countries with a focus on the impact of foreign direct investment (FDI), exports, and free trade. Globalization has opened up opportunities for developing countries to integrate into international markets, attract foreign investment, increase exports, and expand market access. FDI brings benefits in the form of capital, technology, and expertise that help increase productivity and create jobs. Increasing exports contribute directly to economic growth by increasing foreign exchange and strengthening the trade balance. On the other hand, free trade opens up access for local products to the global market, although it also brings competitive challenges for domestic industries. This study finds that, although globalization can accelerate economic growth, dependence on foreign investment and international trade can make developing countries vulnerable to global fluctuations. In addition, economic inequality and sustainability issues are challenges that need to be managed so that the benefits of globalization can be felt more evenly by all levels of society.